Photo-induced transformations in chalcogenide composite layers - Malyovanik, M.; Kikineshi, A.; Messaddeq, S. H.; Messaddeq, Younes [UNESP]; Ivan, I; Ribeiro, SJL (Elsevier B.V., 2004)
Investigations of photo-induced structural transformations (PST) and related changes of optical parameters in the light-sensitive amorphous chalcogenides were extended to composite layers, which consist of a wide band-gap material and an active material, Se60Te40 with a smaller band gap. Photo-stimulated interdiffusion and/or crystallization in layered Se0.6Tc0.4/As0.6Se0.94 and Se0.6Te0.4/SiOx were investigated with respect to their dependence on the compositional modulation of the multilayer at scale-dimensions (similar to3-10nm). It was established that PST due to the interdiffusion and crystallization can be efficiently operated by the composition of the adjacent layers of the multilayer which results in the change of the transformation rate and of the optical relief type (positive or negative). The comparison with a single Se0.6Te0.4 layer and with the known data for amorphous-Se/As2S3 multilayers supports the advantages of composite layers for amplitude-phase optical recording. (C) 2004 Published by Elsevier B.V.